2009
DOI: 10.1002/adsc.200800664
|View full text |Cite
|
Sign up to set email alerts
|

Homobimetallic Ruthenium Vinylidene, Allenylidene, and Indenylidene Complexes: Synthesis, Characterization, and Catalytic Studies

Abstract: Four homobimetallic ruthenium-(pcymene) complexes bearing a tricyclohexylphosphine ligand and polyunsaturated carbon-rich fragments were obtained via a vinylidene-allenylidene-indenylidene cascade pathway from the ethylene complex. All the products were isolated and fully characterized by IR and NMR spectroscopies. The molecular structure of the indenylidene complex 11 was determined by X-ray crystallographic analysis. The catalytic activity of the four complexes was probed in various types of olefin metathesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 96 publications
(78 reference statements)
3
20
0
Order By: Relevance
“…(Scheme 1). Filtering the solid and recrystallization using ethyl acetate/hexane (1:8) yielded 38 % of HL 6 . C 14 …”
Section: Procedures For the Preparation Of Hlmentioning
confidence: 99%
See 1 more Smart Citation
“…(Scheme 1). Filtering the solid and recrystallization using ethyl acetate/hexane (1:8) yielded 38 % of HL 6 . C 14 …”
Section: Procedures For the Preparation Of Hlmentioning
confidence: 99%
“…[3][4][5][6] Except for isomerization, the catalytic properties of these complexes have been investigated in various fields ranging from hydrogen transfer [7][8][9][10][11] to ring-closing metathesis, [4,[12][13][14] etc. The extension of the catalytic activities towards isomerization depends on the metal itself and its structure.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Such NHC·CO 2 zwitterions are rather labile in solution and act as convenient surrogates to air-and moisture-sensitive free carbenes in organometallic synthesis [14] and organocatalysis. [15] For instance, we have successfully used imidazol(in)ium-2-carboxylates as NHC ligand precursors in the synthesis of various second-generation ruthenium-alkylidene catalysts in olefin metathesis, [16] whereas other groups have developed several new major organocatalytic processes based on these zwitterions for carbon dioxide fixation reactions. [17] Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…1) was synthesized and tested in RCM reactions [215]. However, later investigations revealed that the final catalysts formed were actually phenylindenylideneruthenium complexes rather than allenylidene analogs [216][217][218]. This latter homobimetallic ruthenium allenylidene complex was finally synthesized along with other ruthenium homobimetallic complexes and they were tested as catalysts in olefin metathesis [219].…”
Section: Allenylideneruthenium Catalysts In Metathesismentioning
confidence: 99%